Multifunctional human transcriptional coactivator protein PC4 is a substrate of Aurora kinases and activates the Aurora enzymes. (15th February 2016) - Dhanasekaran, Karthigeyan; Kumari, Sujata; Boopathi, Ramachandran; Shima, Hiroki; Swaminathan, Amrutha; Bachu, Mahesh; Ranga, Udaykumar; Igarashi, Kazuhiko; Kundu, Tapas K.
Abstract : Positive coactivator 4 (PC4), a human transcriptional coactivator, is involved in diverse processes like chromatin organization and transcription regulation. It is hyperphosphorylated during mitosis, with unknown significance. For the first time, we demonstrate the function of PC4 outside the nucleus upon nuclear envelope breakdown. A fraction of PC4 associates with Aurora A and Aurora B and undergoes phosphorylation, following which PC4 activates both Aurora A and B to sustain optimal kinase activity to maintain the phosphorylation gradient for the proper functioning of the mitotic machinery. This mitotic role is evident in PC4 knockdown cells where the defects are rescued only by the catalytically active Aurora kinases, but not the kinase‐dead mutants. Similarly, the PC4 phosphodeficient mutant failed to rescue such defects. Hence, our observations establish a novel mitotic function of PC4 that might be dependent on Aurora kinase‐mediated phosphorylation. Abstract : Human transcriptional coactivator PC4 is involved in many processes including chromatin organisation and transcription regulation. PC4 is a highly abundant non‐histone chromatin‐associated protein that is hyperphosphorylated during mitosis. Here, the authors demonstrate that PC4 functions outside the nucleus upon mitotic nuclear envelope breakdown, acting as both a novel substrate and activator of the Aurora kinases. It interacts with Aurora kinase A on centrosomes and with Aurora kinase B at the midbody during mitosis to maintain optimal activity of both kinases, ensuring proper fidelity of mitosis and cytokinesis. This finding could have applications in pathophysiological conditions where fine regulation of Aurora kinase activity is required.